Deconstructing Immigrant Integration: The Case of Kyrgyz Labor Migrants in the United States. Issue 2 (25th January 2020) - Liebert, Saltanat
ABSTRACT: In the aftermath of the dissolution of the Soviet Union, millions of its former citizens moved to other countries. Kyrgyzstan, having experienced painful transition from command to market economy, sends a large share of its workforce abroad, and consequently, receives remittances that amount to one third of its GDP. Thousands of Kyrgyz migrants come to the United States in search of economic opportunities, both legally and through irregular methods. Based on in-depth semi-structured interviews with 42 Kyrgyz labor migrants, this paper examines their economic integration in the United States. The author proposes a conceptual framework that maps out factors influencing how successfully immigrants integrate in the destination countries.